Personalizing Simulations of the Human Atria : Intracardiac Measurements, Tissue Conductivities, and Cellular Electrophysiology - Weber, Frank Michael (Karlsruhe transactions on biomedical engineering / Ed.: Karlsruhe Institute of Technology / Institute of Biomedical Engineering, 2011)
This work addresses major challenges of heart model personalization. Analysis techniques for clinical intracardiac electrograms determine wave direction and conduction velocity from single beats. Electrophysiological measurements are simulated to validate the models. Uncertainties in tissue conductivities impact on simulated ECGs. A minimal model of cardiac myocytes is adapted to the atria. This makes personalized cardiac models a promising technique to improve treatment of atrial arrhythmias.